INOVASI TEKNOLOGI PIROLISIS UNTUK PENINGKATAN KESEJAHTERAAN PETANI KOPI HUTAN DI DESA KRETEK BONDOWOSO - Putri, Resti Pranata; Yudiastuti, Silvia Oktavia Nur; Yossi, Wibisono; Hernowo, Pandit; Handayani, Wiwik; Arumsari, Alif Gita; Halim, Abdul (Jurnal Abdi Insani, 2025)
The Sejahtera Forest Farmers Group (KTH) was established to improve the welfare of the community in Kretek Village, Taman Krocok Subdistrict, Bondowoso Regency. This KTH manages robusta coffee plantations with an annual yield of 500-800 kg. However, for 11 years, the land has not been fertilized, resulting in decreased soil productivity and coffee bean quality. To address this issue, pyrolysis technology was introduced to utilize coffee husk waste. This technology produces biochar, which can enhance soil fertility, bind pollutants, and reduce greenhouse gas emissions. It also produces liquid smoke that can be used as an antimicrobial agent and food preservative. The goal of this activity is to help the community turn coffee husk waste into a valuable product. The method used is participatory rural appraisal, which includes introducing innovations to process coffee husk waste into biochar and liquid smoke, designing and building the equipment, and conducting hands-on practice involving the Sejahtera KTH members. The results of this community service activity show an increase in the knowledge and skills of forest farmers in making biochar and liquid smoke using pyrolysis technology, from 30% to 90%. Overall, this community service program has fostered enthusiasm for utilizing coffee husk waste and enhanced the cohesion of the Sejahtera KTH.